2014
DOI: 10.1002/sia.5403
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth diffusion of oxygen into LDPE exposed to an Ar–O2 atmospheric post‐discharge: a complementary approach between AR‐XPS and Tof‐SIMS techniques

Abstract: aThe in-depth oxygen diffusion into a low density polyethylene film is performed in the post-discharge of an atmospheric plasma torch, supplied in argon as carrier gas and with or without oxygen as reactive gas. The chemical and structural properties of the polymer surface and bulk are studied in terms of plasma parameters (treatment time, power, and reactive gas flow rate). A good correlation between XPS and Fourier transform infrared spectroscopy analyses is demonstrated. The penetration depth of oxygen into… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
(77 reference statements)
1
12
0
Order By: Relevance
“…In previous studies, we have corroborated the necessity of using oxygen to improve the hydrophilicity of LDPE and we have suggested an anisotropic etching mechanism occurring in an atmospheric flowing Ar–O 2 or He–O 2 post‐discharge. For instance, we have shown that an Ar–O 2 flowing post‐discharge treatment induces a decrease in advancing water contact angles (aWCA) as a function of treatment time, until a plateau around 40° is reached after 30 s. This plateau, suggesting a saturation of the oxygenated functions (three polar functionalities, i.e., C–O, CO, and O–CO) on the surface has lead us to study the diffusion of oxygen into the bulk of the film (subsurface) . We consider here as “subsurface” the sample's region located immediately below the outer surface and that is not in direct contact with the gaseous species of the plasma phase.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…In previous studies, we have corroborated the necessity of using oxygen to improve the hydrophilicity of LDPE and we have suggested an anisotropic etching mechanism occurring in an atmospheric flowing Ar–O 2 or He–O 2 post‐discharge. For instance, we have shown that an Ar–O 2 flowing post‐discharge treatment induces a decrease in advancing water contact angles (aWCA) as a function of treatment time, until a plateau around 40° is reached after 30 s. This plateau, suggesting a saturation of the oxygenated functions (three polar functionalities, i.e., C–O, CO, and O–CO) on the surface has lead us to study the diffusion of oxygen into the bulk of the film (subsurface) . We consider here as “subsurface” the sample's region located immediately below the outer surface and that is not in direct contact with the gaseous species of the plasma phase.…”
Section: Introductionsupporting
confidence: 78%
“…As the RF power applied to the two torches is 90 W, the surface plasma power density estimated on Σ is 0.36 W/mm 2 for the linear plasma torch, and 0.28 W/mm 2 for the showerhead plasma torch. As explained in earlier works, this difference can be considered as negligible as plasma power variations over this range does not induce significant surface modification in terms of aWCA, mass losses, roughness, or chemical surface composition . Those values are reported in Table .…”
Section: Experimental Set‐upmentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, most of the highly energetic particles of the plasma, such as electrons and ions, are neutralized before reaching the polymer substrate. So the plasma‐polymer interactions mainly occur by means of excited species and radicals and they remain confined in the outermost atomic layers of the polymer . A typical example of surface modification concerns the polyolefins and, more specifically polyethylene, employed in a multitude of applications from the everyday life, such as food packaging and medicine, to the highly technological ones in the automotive and electronics fields.…”
Section: Introductionmentioning
confidence: 99%
“…A known route to improve the adhesion of the polyolefins consists in the so‐called oxidative functionalization, usually obtained by the use of O 2 as reactive gas, that induces the grafting of O‐containing functional groups. The literature reports a series of recent works carried out with atmospheric Ar/O 2 or He/O 2 post‐discharges for improving the hydrophilicity of LDPE or HDPE (high density polyethylene) . This result is obtained by the grafting of three polar functionalities –C–O, CO and O–CO– whose densities on the polymer surface decrease with increasing the treatment time.…”
Section: Introductionmentioning
confidence: 99%